Modelling and identification of time-domain electromagnetic fields of an antenna - Luz Benevides, Rafael Rodrigues (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.